PENDIDIKAN KEHIDUPAN YANG MERDEKA RUANG DAN WAKTU MASYARAKAT SAMIN SUKOLILO, PATI - Agus Supratikno; Suwarto Adi (Jurnal Dinamika Pendidikan, 2021)
This paper is the result of research on the Samin Community Education Model in Ngawen Hamlet, Sukolilo, Pati. They do not send their children to formal schools. Their decision not to send their children to formal schools was motivated by the history of the Samin Suronsentiko movement against Dutch colonialism. In their collective memory, there is a memory that the Dutch are smart but their intelligence is used to fool others. Another reason why they do not send their children to formal schools is that there is an obligation for their children to attend lessons in other religions that are not their beliefs. How does the education of the Samin community compare to Romo Mangun's vision of true learning that is liberating and contextual, not limited by time and space and is carried out throughout life. This type of research is descriptive qualitative research. The main data collection techniques are carried out through observation, in-depth interviews, and documentation. Meanwhile, secondary data collection is done through literature study. From the results of research and comparative studies, it is found that the education model of the life of the Samin community that is independent of time and space, although very simple, is in some way consistent with Romo Mangun Wijaya's educational vision. Keywords: Education Model, Freedom of learning, Space and time, Samin